A natural adaptive syndrome as a model for the origins of cereal agriculture. Issue 1875 (28th March 2018) - Wood, David; Lenné, Jillian M.
Abstract : A novel explanation of the origin of cereal agriculture is proposed, based on the ecology and adaptive morphology of wild cereals ancestral to our founder cereals (einkorn, emmer and barley). Wild cereals are unusually large-seeded. A natural evolutionary-ecological syndrome relates l arge seed, a wns and m onodominance (LAM). Awns bury attached seeds in the soil, protecting seed from fire; buried seed needs to be large to emerge on germination; large seeds, growing without competition from small-seeded plants, will produce monodominant vegetation. Climatic and edaphic instability at the Pleistocene–Holocene boundary would have provided an impetus for the spread of annual ruderal grasses. LAM grassland provided an obvious natural model for the origins of cereal agriculture. Subsequent field management would mimic the natural niche (MNN). The fact that monodominance is a long-standing character of the natural LAM syndrome validates cereal monocultures (now producing most of our food). An alternative explanation of crop domestication, by auditioning a great range of species for a human-constructed niche (NCT), is rejected.